2006
DOI: 10.1086/498578
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cord Blood Immune Effector‐Cell Responsiveness Mediated by CD4+Cells Induced in Utero as a Consequence of PlacentalPlasmodium falciparumInfection

Abstract: To determine mechanisms of neonatal parasite antigen (Ag)-specific immune suppression associated with placental Plasmodium falciparum infection, we isolated cord blood mononuclear cells (CBMCs) from Gabonese neonates born to mothers with differing histories of P. falciparum infection and performed ex vivo and in vitro studies to evaluate immune regulatory activity. We found increased ex vivo percentages of CD4(+)CD25(hi) and CD4(+)CD25(+)CTLA-4(+) cells and increased interleukin (IL)-10 responses to parasite A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
5
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 39 publications
6
100
5
5
Order By: Relevance
“…Our findings would support this hypothesis. We found no effect of PM on ex vivo CD4 be increased by PM [24], whereas another Gambian study found no effect of PM on ex vivo CD4 1 CD25 1 T cells [21].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Our findings would support this hypothesis. We found no effect of PM on ex vivo CD4 be increased by PM [24], whereas another Gambian study found no effect of PM on ex vivo CD4 1 CD25 1 T cells [21].…”
Section: Discussioncontrasting
confidence: 85%
“…hi or CD4 1 CD25 1 T cells leads to decreased parasite Ag-specific IL-10 responses and enhanced IFN-g reactivity [21,24]. The latter study demonstrated that the CD4 1 CD25 1 cells express higher levels of FOXP3 by reverse transcription PCR than their CD4 1 CD25 counterparts [21].…”
Section: Cd25mentioning
confidence: 86%
“…of T cells of newborns born to mothers with malaria and neonatal pups of mice infected with Plasmodium yoelii demonstrate that immunoregulatory lymphocytes of newborns are capable of suppressing malaria Ag-driven T cell responses or inducing T cell anergy (29,32,33). Taken together with the demonstration of immune tolerance to filarial parasites by a mechanism of prenatal exposure in the context of maternal infection during gestation (34,35), these findings suggest that intravascular pathogens that chronically infect women during their childbearing years may result in de facto immune tolerance when infants and children are challenged with natural infection later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Archived samples from a malaria in pregnancy study, carried out in an area of Gabon characterized by stable meso-to hyperendemic malaria transmission, were used for this study. 17 Paired maternal and umbilical cord-blood samples were obtained at time of parturition from pregnant women attending the Albert Schweitzer Hospital in Lambarene, Gabon from July 2000 to February 2004. Medical records of the mothers were examined to determine whether malaria episodes were detected and appropriately treated during pregnancy.…”
Section: Methodsmentioning
confidence: 99%